1989
DOI: 10.1088/0741-3335/31/2/006
|View full text |Cite
|
Sign up to set email alerts
|

RFP stability with a resistive shell in HBTX1C

Abstract: Results are presented from thin (resistive) shell experiments on HBTX and compared with theoretical (linear and non-linear) studies of the plasma stability. Current pulses of 3--5 ms are obtained, compared with the shell time constant for vertical field penetration of 0.5 ms. Theoretically predicted thin shell modes, phase locked to the wall, are prominent experimentally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
67
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 6 publications
4
67
0
Order By: Relevance
“…[3][4][5][6][7][8][9][10][11] In RFPs, apart from the first observation of RWM reported in HTBX1C in 1988, 12 numbers of studies have been reported in recent years, both experimentally and theoretically; [13][14][15][16][17][18][19] in particular, the successful feedback control of multiple unstable RWMs has shown to be achieved by the equipments implemented in the experiments. [17][18][19] For instance, in RFX-mod 20 experiments, the observations give an evidence that the system of the active control has a sufficient efficiency and a large flexibility 18 and therefore can provide an excellent environment to apply and/or to test RWM physical modeling and various control scenarios, 21 which can further provide a better understanding for RWM physics and the control strategy.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11] In RFPs, apart from the first observation of RWM reported in HTBX1C in 1988, 12 numbers of studies have been reported in recent years, both experimentally and theoretically; [13][14][15][16][17][18][19] in particular, the successful feedback control of multiple unstable RWMs has shown to be achieved by the equipments implemented in the experiments. [17][18][19] For instance, in RFX-mod 20 experiments, the observations give an evidence that the system of the active control has a sufficient efficiency and a large flexibility 18 and therefore can provide an excellent environment to apply and/or to test RWM physical modeling and various control scenarios, 21 which can further provide a better understanding for RWM physics and the control strategy.…”
Section: Introductionmentioning
confidence: 99%
“…RFX-mod has demonstrated the possibility to overcome these limitations with the active control of the edge radial field, made possible by a grid of active coils, placed outside the shell, fully covering the torus. The first scheme tested, the so-called intelligent-shell (IS) [4], in which the coils are coupled in a feedback scheme with the measurements provided by an identical grid of radial field sensors, improves the plasma performances by preventing the radial field penetration of the shell [5]: besides a complete suppression of the resistive wall modes [6], the TMs edge amplitude is kept at a low value. In RFPs TMs in the non-linear regime are required by the dynamo mechanism in order to maintain the reversed configuration [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The RWM has been identified in a number of devices. 9,10 The advanced tokamak program is addressing means by which to stabilize the RWM by using active methods to control the plasma rotation, 11 and by using feedback with magnetic coils. [12][13][14] The Gimblett double wall configuration does not require active means to suppress an instability.…”
Section: Introductionmentioning
confidence: 99%